Effects of Integrated Application of Vermicompost and Inorganic Fertilizers on Selected Soil Characteristics and Productivity of Wheat (Triticum aestivum L.) and Faba Bean (Vicia faba L.) in Dire and Legedadi Watersheds of Ethiopia - Meseret Habtamu; Eyasu Elias; Teshome Soromessa; Mekuria Argaw (Applied and Environmental Soil Science)
The adoption of integrated soil fertility management (ISFM) practices can improve soil quality and sustainably increase crop yield while slowing down the rate of ongoing degradation. This research assessed the effects of selected ISFM practices on soil properties at the Dire and Legedadi watersheds, central highlands of Ethiopia, in the 2021 and 2022 cropping seasons. Eight treatments were selected (sole wheat, sole faba bean, 100% recommended NPS + urea fertilizers, 100% recommended vermicompost (VC), wheat with half dose both NPS + urea and VC, wheat and faba bean intercropping with half dose both NPS + urea and VC, wheat and faba bean intercropping with half-dose NPS + urea fertilizers, and wheat and faba bean intercropping with 50% VC). The treatments were studied on farmers’ fields using a randomized complete block design with three replications. Analysis of variance showed that soil samples collected from each plot indicated significant differences in soil organic carbon (SOC), total nitrogen (TN), available phosphorus (Pav), exchangeable bases (Ca2+, Na+, and Kexc), and cation exchange capacity (CEC). Soil pH and moisture showed improvement in combined fertilizers application compared to the preplanting soil sample. A combined application of VC and NPS + urea fertilizers significantly (p<0.05) increased SOC, Pav, K+, Na+, and CEC compared to the control. A combined application of VC and NPS + urea fertilizers improved the soil quality. The highest TN contents of 0.36% at the Dire site and 0.30% at the Legedadi site were obtained with the full dose VC treatment. Additionally, this treatment resulted in the greatest water-holding capacity and soil carbon stock at both sites. Similarly, the wheat-faba bean intercropped plots showed a significant (p<0.05) effect on the soil carbon stock and sequestration over the control in both study sites. Based on the results of the current study, it can be concluded that the combined application of a half dose of each VC and NPS + urea fertilizers improved most soil physicochemical properties at both sites. This suggests that using a combination of VC and NPS + urea fertilizers can help farmers reduce their inorganic fertilizer needs by 50%.